Total Synthesis of Stemoamide, 9a-epi-Stemoamide, and 9a,10-epi-Stemoamide: Divergent Stereochemistry of the Final Methylation Steps - Siitonen, Juha H.; Csókás, Dániel; Pápai, Imre; Pihko, Petri M. (Synlett, 2020)
Total syntheses of stemoamide, 9a-epi-stemoamide, and 9a,10-epi-stemoamide by a convergent A + B ring-forming strategy is reported. The synthesis required a diastereoselective late-stage methylation of the ABC stemoamide core that successfully enabled access to three of the four possible diastereomeric structures. For the natural stemoamide series, the diastereoselectivity can be rationalized both by kinetic and thermodynamic arguments, whereas for the natural 9a-epi-stemoamide series, the kinetic selectivity is explained by the prepyramidalization of the relevant enolate.
Keywords: total synthesis; Stemona alkaloids; cyclic stereocontrol; Mukaiyama–Michael reaction; DFT calculation